Outcomes of a tribal community program on hepatitis C, HIV, and syphilis screening, confirmation testing, and treatment initiation for an underserved population - Comiford, Ashley; Mera, Jorge; Lewis, Kendra; Christy, Savana; Feder, Molly; Blair, Andrea (Frontiers in Public Health, 2025)
BackgroundAmerican Indian and Alaska Native people are disproportionately impacted by hepatitis C, HIV, and syphilis, with rates 2.3, 1.9, and 6.4 times that of non-Hispanic White people, respectively. The objective was to describe the first 9 months implementing a community-based tribal program to screen and link underserved people to hepatitis C, HIV, and syphilis care and treatment. An additional objective was to identify patient characteristics associated with completing confirmation testing when indicated.MethodsThis study occurred from January through September 2024 on the Cherokee Nation reservation in Oklahoma. Survey and medical record data from Cherokee Nation’s Hepatitis C Engagement and Linkage Program, a collaboration between the Cherokee Nation Health Services and community programs servicing people with substance use disorders and/or reduced healthcare access. People 18 years and older who visited the organizations during the project period and provided consent were eligible. Project outcomes, including point of care screening results, receipt of confirmation testing, test results, and treatment initiation, were assessed using counts and proportions. Associations between patient characteristics and completion of confirmation testing were assessed using Chi-square or Fisher’s exact tests.ResultsThe program screened 503 people, including 365 American Indian and Alaska Native people, for hepatitis C, HIV, and syphilis. Forty-five percent of participants reported lifetime injection drug use. Overall, 102 (20%) participants had a reactive hepatitis C antibody test, 36 (35%) of whom received confirmatory hepatitis C RNA testing. Sixteen people were diagnosed with hepatitis C infection, 12 (75%) of whom initiated treatment. Sixty participants (12%) had a reactive Treponema pallidum syphilis antibody test, 18 (30%) of whom received confirmatory testing. Seventeen people were diagnosed with untreated syphilis, 16 (94%) of whom initiated treatment. Less than 1% of participants had a reactive HIV antibody test, although specific numbers are suppressed due to a small sample size. Most people who were linked to care beyond antibody testing were American Indian and Alaska Native.ConclusionCherokee Nation successfully screened underserved individuals for hepatitis C, HIV, and syphilis with moderate success in further evaluation and treatment. Future interventions should include onsite treatment options to prevent barriers to accessing healthcare.